Transformative Learning for Controversial History of G 30 S/PKI (History Department, Semarang State University and Historian Society of Indonesia, 2020)
G 30 S/PKI is a controversial issue in Indonesian history and a sensitive material because of past traumatic memories. It is a challenge for history teachers in learning in schools. This research aims to analyze the controversial history material of the G30 S/PKI in history textbooks in school and formulate the learning concepts that are relevant for the controversial history. This type of research is qualitative with the content analysis. The data source is the history textbook and any other sources appropriate. The results show that in the Indonesian History Book for grade XII, 7 (seven) versions of the theory of the G30 S/PKI are presented. The various versions need to be integrated into the substance of the G30 S/PKI incident material so that it reflects the balance in the construction of the content with its arguments and weaknesses. In learning, the concept of transformative learning that is directed at historical didactics based on academic history is needed. History learning introduces educational content to build awareness of values. Students are actively involved through cooperative learning accompanied by exploration activities related to G 30 S/PKI material. Learning is directed at active historical thinking that opens an open dialogue. In this way, the teaching of controversial material history has the potential for character education (critical, analytical, objective, open-minded) that relies on internalization to minimize indoctrination. G 30 S/PKI merupakan isu kontroversial dalam pembelajaran sejarah Indonesia dan materi yang sensitif karena memori traumatik masa lalu. Hal tersebut menjadi tantangan bagi para guru sejarah dalam pembelajaran di sekolah. Penelitian ini bertujuan untuk menganalisis materi sejarah kontroversial G 30 S/PKI dalam buku pelajaran sejarah di sekolah menengah atas dan merumuskan konsep pembelajaran yang relevan untuk materi sejarah kontroversial. Jenis penelitian kualitatif dengan analisis isi. Sumber data berupa buku teks sejarah di sekolah dan sumber lain yang relevan. Hasil penelitian menunjukkan bahwa dalam buku Sejarah Indonesia SMA kelas XII Kurikulum 2013 dipaparkan 7 (tujuh) versi teori tentang G 30 S/PKI. Berbagai versi tersebut perlu diintegrasikan ke dalam substansi materi sehingga mencerminkan keseimbangan dalam konstruksi materinya dengan argumentasi dan kelemahan-kelemahannya. Dalam pembelajaran diperlukan konsep pembelajaran transformatif yang diarahkan pada didaktik historis berbasis historis akademik. Pembelajaran sejarah mengintroduksi muatan-muatan edukatif untuk membangun kesadaran nilai. Siswa terlibat aktif melalui pembelajaran kooperatif yang disertai kegiatan-kegiatan eskplorasi materi G 30 S/PKI. Pembelajaran diarahkan pada active historical thingking yang membuka dialog terbuka. Dengan cara demikian, pembelajaran sejarah materi kontroversial potensial bagi pendidikan karakter (kritis, analitis, objektif, terbuka) yang bertumpu pada internalisasi untuk meminimaliasasi indoktrinasi.